Tinjauan Hukum Ekonomi Syariah Terhadap Kenaikan Harga Beras di Nusa Tenggara Barat - Muhammad Masruron; Matlaul Ipan (TAFAQQUH, 2024)
Indonesia is experiencing an increase in rice prices nationally, especially in West Nusa Tenggara. The NTB Province Central Statistics Agency (BPS) stated that the increase in rice prices in NTB in September 2023 will reach 46 percent. This increase was due to the impact of the long dry season or El Nino. This quite high increase in rice prices caused inflation in NTB. This research aims to determine the practice of increasing rice prices in the people of Nusa Tenggara Bara. The type of approach used in this research is a descriptive qualitative approach. Data collection in this research method uses observation and documentation methods. The research results show that West Nusa Tenggara is experiencing a rice surplus. Still, the reality is different from the real conditions, namely price increases in the region, so there needs to be serious monitoring, including from a policy perspective, especially restrictions on outbound rice distribution. Because what takes priority first is the needs of the local community which must be met. The increase in rice was caused by national prices not being the same as regional conditions, which caused price increases. In a market mechanism, the demand and supply sides must be balanced. Islam provides the view that the interests of the ummah are more important than other needs.